ADAPTATION OF EMPLOYEES IN THE CONDITIONS OF IMPLEMENTATION OF NEW TECHNOLOGIES AND AUTOMATION - Umarova Nilufar Jaloliddin kizi (Bright Mind Publishing, 2025)
This article explores the challenges and strategies associated with employee adaptation amid the implementation of new technologies and automation in the workplace. As technological innovation accelerates across industries, the need for workforce flexibility and adaptability becomes more critical. The paper analyzes key factors influencing successful employee integration into digitally transformed environments and highlights practical mechanisms for improving professional readiness. Emphasis is placed on the experience of Uzbekistan’s labor market, where digital transformation is rapidly progressing and reshaping job roles, tasks, and required competencies.
Keywords: Employee adaptation, digital transformation, automation, labor market, upskilling, technology integration, workforce development.